Obstructive Sleep Apneu (OSA), Obesitas Hypoventilation Syndrome (OHS) dan Gagal Napas: [Obstructive Sleep Apnea, Obesity Hypoventilation Syndrome, and Respiratory Failure] - Mokhammad Mukhlis; Arief Bakhtiar (Jurnal Respirasi, 2015)
Background: Obstructive sleep apnea (OSA) is a state of the occurrence of upper airway obstruction periodically during sleep that causes breathing to stop intermittently, either complete (apnea) or partial (hipopnea). Obesity hypoventilation syndrome (OHS) is generally defined as a combination of obesity (BMI ≥ 30 kg / mc) with arterial hypercapnia while awake (PaCO2 > 45 mmHg) in the absence of other causes of hypoventilation. Purpose: In order for the pulomonologis can understand the pathogenesis and pathophysiology of OSA and its complications. Literature review: Several studies have been expressed about the link between OSA, OHS with respiratory failure disease. Pathophysiology of OSA, OHS in respiratory failure were difficult to detect, can cause respiratory failure disease management becomes less effective. Conclusion: A good understanding can help with the diagnosis and management of the appropriate conduct to prevent complications of respiratory failure associated with OSA.